2009
DOI: 10.3354/meps07730
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton biodiversity and NW Mediterranean Sea warming: changes in the dinoflagellate genus Ceratium in the 20th century

Abstract: Our knowledge of the response of phytoplankton to climate change is restricted by the lack of phytoplankton long-term studies, especially those reporting species data. To circumvent this problem, we combined recent data from sampling at monitoring sites with old bibliographic data. The study was conducted on the genus Ceratium (planktonic dinoflagellates) in the NW Mediterranean, as numerous studies have been conducted in the area since the beginning of the 20th century. In addition, species of this highly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
2
24
0
1
Order By: Relevance
“…Similarly, warming increased the abundance of ciliates and decreased the development time of copepods in mesocosms deployed in the Thau Lagoon (Vidussi et al 2011). Over longer periods of time (within the last 100 yr), warmer sea surface temperatures changed the community composition of the Ceratium genus in Villefranche Bay due to the disappearance of some stenotherm species (Tunin-Ley et al 2009). Laboratory experiments have shown that a small increase in temperature per generation time (0.1 to 0.2°C) may increase the risk of extinction of herbivorous protists, and microbial communities may become dominated by bacterivores (Petchey et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, warming increased the abundance of ciliates and decreased the development time of copepods in mesocosms deployed in the Thau Lagoon (Vidussi et al 2011). Over longer periods of time (within the last 100 yr), warmer sea surface temperatures changed the community composition of the Ceratium genus in Villefranche Bay due to the disappearance of some stenotherm species (Tunin-Ley et al 2009). Laboratory experiments have shown that a small increase in temperature per generation time (0.1 to 0.2°C) may increase the risk of extinction of herbivorous protists, and microbial communities may become dominated by bacterivores (Petchey et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The Ceratium species are known from warm waters of the Tasman Sea (Hallegraeff et al 2010) and, considering the season, we suggest that the strengthening EAC was responsible for their appearance in southern Tasmania. The poleward extension of tropical and warmtemperate Ceratium species has been well documented in the Northern Hemisphere (Dodge and Marshall 1994;Johns et al 2003;Barnard et al 2004;Hays et al 2005;Edwards et al 2006), and it is predicted that subsequent expansions will occur into the future (Turin-Ley et al 2009). As Tasmania is expected to experience continued ocean warming into this century (Ridgway and Hill 2009), it follows that introductions of Ceratium, and perhaps other warm water species, will also be observed.…”
Section: Discussionmentioning
confidence: 99%
“…It is acknowledged that species of Ceratium may exert a seasonal competitive advantage over other microphytoplankton, as they are able to tolerate a wide range of environmental conditions (Baek et al 2007). Some studies suggest that a mixotrophic feeding strategy contributes to a competitive advantage (Mikaelyan and Zavyalova 1999; Smalley et al 1999;Turin-Ley et al 2009), allowing Ceratium species to overcome nutrient depleted waters above the thermocline and light depleted waters below the thermocline. Others highlight Ceratium as a poor food option for most species of grazing zooplankton due to their large size (Graneli et al 1989) and characteristic shapes (Hargrave and Geen 1970).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceratium Schrank, an armoured dinoflagellate genus has been considered a biological model for a wide range of studies as utilized by TuninLey et al (2007TuninLey et al ( , 2009. One of the several advantages offered by this genus is that identification of species level is more feasible than other phytoplankton group (Tunin-Ley et al 2009). Apart from this, Ceratium is known for its sensitivity to temperature in terms of biogeography (Dodge & Marshall 1994), seasonality and morphology (Sournia 1967).…”
mentioning
confidence: 99%